STUDI PENINGKATAN DAYA ADSORPSI KARBON AKTIF TERHADAP KADAR PEROKSIDA DENGAN PENAMBAHAN AKTIVATOR - Wardatul Husna Irham (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2015)
Activator that has been successfully used in the process of activation of activated carbon from coconut shell is Na2CO3, NaCl, HCl, H2SO4 and NaOH. The addition of activator in the activated charcoal will enlarge the surface area of the charcoal with open pores are closed, so as to increase the adsorption capacity of activated carbon. In the process of making activated carbon from coconut shell charcoal, carbon obtained randemen quite high, ranging from 80 to 81.74 wt% of carbon initially obtained with water content ranging from 2.2864 to 3.9489% and ash content of 2.04 to 3.28%. This means that the active carbon can be used as an activated carbon is good, because it meets the standards SII quality activated carbon. From the results obtained can be seen that the solution of HCl, NaOH and Na2CO3 can be used as an activator of activated carbon in the lower levels of peroxide. The addition of these activators can enlarge the surface area of the carbon that is by breaking the bonds of hydrocarbons or oxidizing surface molecules. Based on the research results, the best solution is used as an activator of activated carbon in adsorbing peroxide is an alkaline solution that is equal to 91.11% of the initial peroxide content.